HUBUNGAN ANTARA KARAKTERISTIK DOKTER DENGAN KELENGKAPAN PENGISIAN LEMBAR RINGKASAN KELUAR - Ni Luh Putu Devhy (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2014)
AbstractThis study is aimed to evaluate the performance of doctors in completing medical record in terms of thecharacteristics of the doctors. The type of this research is analytic research which is examined the relationshipbetween characteristics the doctor, such as age, work period, knowledge of the medical record, gender, type ofexpertise, education and the employment status with the completeness of filling out the summary sheet (doctor’sresume). The samples used 374 medical record documents and 7 doctors. The obtained data will be analyzedthrough Multiple Logistic Regression. The results of this study shows that the variables have a relationshipwith the completeness of filling out the Summary Sheet ( Doctor’s Resume) are the knowledge of the medicalrecord, work period and medical education with a strong relationship category. While based on multivariateanalysis, shows that these three variables also affect the completeness of filling out Summary Sheet (Doctor’sResume). Doctors who have knowledge of the medical record, work period >5 years and taking non specialistmaster’s degree can fill the completeness of the medical record documents properly. The author gives adviceto the General Hospital District dr. Soeratno Gemolong Sragen for holding training, education and medicalrecord seminars to the doctors seminars to improve the completeness of the medical record documents.Keywords: Characteristics of Doctors, Completed Analysis, Doctor’s ResumeAbstrakPenelitian ini dilakukan untuk mengevaluasi kinerja dokter dalam melengkapi rekam medis ditinjau darikarakteristik dokter tersebut. Jenis penelitian ini adalah observasional analitik. Sampel penelitian yaitu374 dokumen rekam medis dan 7 orang dokter. Analisis data dengan menggunakan regresi logistik ganda.Hasil penelitian menunjukkan bahwa pengetahuan tentang rekam medis, masa kerja dan pendidikan dokterberpengaruh terhadap kelengkapan pengisian Lembar Ringkasan Keluar (Resume Dokter). Dokter yangmemiliki pengetahuan tentang rekam medis, masa kerja > 5 tahun dan menempuh pendidikan S2 non spesialisdapat mengisi kelengkapan dokumen rekam medis dengan baik.Kata kunci: Karakteristik Dokter, Analisis Kelengkapan, Resume Dokter